1998
DOI: 10.1007/bf03395277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Predator-Induced Stress and Age on Working Memory in Rats

Abstract: The effects of age and predator-induced stress, by exposing rats to a cat, were examined during subsequent testing of spatial working memory. Male rats (3 months and 20 months of age) were trained on a spatial delayed-alternation task using an elevated T maze. After subgroups were given intermittent protected-exposure sessions over a 3-day period to cats or to a control condition, they were tested on the working memory task. The old rats took more trials to reach training criterion. Overall , both stress-expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
3
1
Order By: Relevance
“…Although scant, there are some previous studies in male rats showing that chronic stress does not alter spatial working memory, but the present data greatly extend these findings. Yet, it should be underscored that while our current findings are in agreement with some previous studies showing that chronic stress had no effect on working memory (Luine et al, 1994(Luine et al, , 1996Williams et al, 1998) or may be causing impaired memory retrieval while leaving working memory intact (Srikumar et al, 2006(Srikumar et al, , 2007, they are inconsistent with previous findings reported by Mizoguchi et al (2000) and Manikandan et al (2006) showing that chronic stress impaired spatial working memory or both reference and working memory. This could be due to methodological differences, such as the type and duration of stress and the memory test used.…”
Section: Discussioncontrasting
confidence: 95%
“…Although scant, there are some previous studies in male rats showing that chronic stress does not alter spatial working memory, but the present data greatly extend these findings. Yet, it should be underscored that while our current findings are in agreement with some previous studies showing that chronic stress had no effect on working memory (Luine et al, 1994(Luine et al, , 1996Williams et al, 1998) or may be causing impaired memory retrieval while leaving working memory intact (Srikumar et al, 2006(Srikumar et al, , 2007, they are inconsistent with previous findings reported by Mizoguchi et al (2000) and Manikandan et al (2006) showing that chronic stress impaired spatial working memory or both reference and working memory. This could be due to methodological differences, such as the type and duration of stress and the memory test used.…”
Section: Discussioncontrasting
confidence: 95%
“…Moreover, a single session of exposure to inescapable shock was found to interfere with many types of associative learning tasks, such as shuttlebox escape learning (e.g., Maier, 1984), appetitive instrumental learning (e.g., Roseliini, 1978), and position escape learning in a Y maze (Jackson et aI., 1980). More recently, Williams et al (1998) reported that an acute ethological stressor of exposing rats, in a protective cage, to a cat significantly disrupted their asymptotic-level performance on a spatial delayedalternation task used to assess working memory.…”
Section: Methodsmentioning
confidence: 99%
“…Experiment 3 incorporated some of the methodology used by Williams et al (1998) to determine if exposure to TMT might effectively interfere with spatial working memory (i.e., SWM) on a delayedalternation task using water as a reinforcer. Another objective of this research was to examine if low versus high amounts of TMT, relative to equivalent amounts of the novel odor of citronella (CIT), would have differential effects on the subsequent delayed-alteration performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation